Perceptions of Construction Professionals in Addressing the Issue of Data Ownership in Building Information Modelling - James, Christabelle Jemin; Mohd Said, Naqiyatul Amirah (Research in Management of Technology and Business, 2024)
Building Information Modelling is a collaborative process that enhances communication and productivity among construction professionals. If the data ownership is not recognised, this can lead to data ownership issues in BIM. This study attempt to identify data ownership issues in BIM faced by the construction professionals and to identify the strategies to overcome the issues. Qualitative research method through semi-structured interviews were conducted with five experts in this area. The interview conducted aiming to discover their understanding on BIM data ownership, issues faced by the professionals and strategies to overcome the issues of data ownership in BIM-enabled projects. It can be identified that the issues faced by the construction professionals are difficulties to determine the ownership of BIM model, no standardisation on company guidelines on BIM data use, and conflict among construction professionals. Therefore, the roles and responsibilities of construction team must be clearly distinguished, CDE’s security should be enhanced and the current protocol and agreements on BIM data ownership in the project must be emphasized. By considering these issues and strategies, the project parties can work better with each other in the collaborative environment, hence, enhancing the work productivity during project and allow better communication among them.